A Study on Aerodynamic Effect of a Generic Car Spoiler Using Computational Fluid Dynamics (CFD) - Shafee, Lokman Hakim; Sapit, Azwan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Most of the time, the car normally breaks through the air barrier when a human drivesthe vehicle. In an undesired condition where the handling and stability of the car candeteriorate as a result of tires losing the traction to the road because of lift, it can beencountered by installing the spoiler. In this research work, the properties of air flowhave been investigated around the spoiler where the value of the drag and lift forcesand its coefficient has been computed. The research is to distinguish the forces actingon three types of spoiler with a varied angle of attack and subjected to differentvelocity. Ansys Fluent is utilised to analyse and simulate a computational fluiddynamic (CFD) technique. It can be seen the angle of attack and velocity affected themagnitude of lift and drag force and their coefficient. At velocity = 45 m/s, all spoiler1, 2 and 3 experienced downforce with lift coefficient at -0.02632, -0.03705 and -0.08887, respectively. For this kind of spoiler, the adjustment of angle of attack onspoiler 2 at 10° AOA could be ideal in terms of lift and drag coefficient optimizationbased on the Lift over Drag Ratio recorded at 4.56. The best spoiler design should havethe least drag coefficient and considerably higher negative lift coefficient.